2017
DOI: 10.1371/journal.pone.0188803
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions for skin infections among Western Australian children and adolescents from 1996 to 2012

Abstract: The objective of this study was to describe the occurrence of skin infection associated hospitalizations in children born in Western Australia (WA). We conducted a retrospective cohort study of all children born in WA between 1996 and 2012 (n = 469,589). Of these, 31,348 (6.7%) were Aboriginal and 240,237 (51.2%) were boys. We report the annual age-specific hospital admission rates by geographical location and diagnostic category. We applied log-linear regression modelling to analyse changes in temporal trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…We conducted a population‐based retrospective cohort study of WA births between 1996 and 2012 (n = 469 589, of which 31 348, 6.7% were Aboriginal). Further details on the cohort are provided elsewhere . Ethical approval was obtained from the Western Australian Department of Health Human Research Ethics Committee and the WA Aboriginal Health Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a population‐based retrospective cohort study of WA births between 1996 and 2012 (n = 469 589, of which 31 348, 6.7% were Aboriginal). Further details on the cohort are provided elsewhere . Ethical approval was obtained from the Western Australian Department of Health Human Research Ethics Committee and the WA Aboriginal Health Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…The point prevalence of scabies has been reported to range from 5% to 35% in remote Australian contexts, with Aboriginal children also having one of the highest reported prevalences in the world, a burden only surpassed by Panama (78%) and Fiji (44%) . Whilst skin infections are generally viewed as a primary care issue, we have previously identified in WA that 14.8% of Aboriginal children and 1.5% of non‐Aboriginal children are hospitalised at least once for skin infections (1996‐2012) during childhood, with rates in Aboriginal infants 20 times that of their non‐Aboriginal counterparts . We have also confirmed that skin infections are under‐reported in hospitalised patients due to under‐recognition and normalisation, suggesting that the burden of skin infection hospitalisations might be substantially higher …”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of all children admitted to hospital in two regional centres studied had a skin infection (49% had impetigo and 8% had scabies), and in these high prevalence settings, health care workers were under‐reporting skin infections . Linked hospitalisation data for all children born in WA between 1996 and 2012 ( n = 469 589), of whom 6.7% were Aboriginal, found that hospitalisation rates for skin infections were 15 times higher for Aboriginal children than non‐Aboriginal children (95% CI, 14.5–15.5; P < 0.001), and most commonly they were for abscesses (42.2%), cellulitis (26.0%), impetigo (14.3%) and scabies (15.8%) …”
Section: Epidemiology Of Skin Infections In Australian Aboriginal Chimentioning
confidence: 99%
“…The burden of abscesses disproportionately affects Aboriginal children. Skin abscesses are the most common reason for skin‐related hospitalisation in Aboriginal children in WA, accounting for almost half of all admissions to hospital for skin diseases, and the hospital length of stay is longer for Aboriginal children …”
Section: Epidemiology Of Skin Infections In Australian Aboriginal Chimentioning
confidence: 99%
See 1 more Smart Citation